PELATIHAN DARING FINANCIAL LIFE SKILLS: ALTERNATIF LITERASI KEUANGAN DI MASA PANDEMI - Septina, Nina; Djajadikerta, Hamfri; Setiawan, Amelia; Danil, Lilian; Susilo, Agustinus; Fitriani, Katlea (Jurnal Pengabdian Sosial, 2021)
ABSTRACT Responding to policies issued by the government through the Ministry of Education and Culture on the learning process during the pandemic, universities adjusted every form of tridharma activities held, including community service activities. One of the cooperation activities between Parahyangan Catholic University and Astra through the Kampung Berseri Astra program in its implementation also needs to be adjusted. One out of some capacity building activities by  the community service team at BUMDes Maju, Bumdes Jiwa Ilir and BUMDes Bermuda in Indramayu Regency is through the implementation of online training on financial literacy. Participants consisted of BUMDes managers, SMEs and residents from Ujunggebang Village, Ilir Village and Kedokanagung Village. Because the activities were carried out online, some participants also came from students and MSMEs in West Java. The enthusiasm of the participants was reflected in the activeness during the training session, the number of comment responses and questions submitted through chat boxes during the activity, as well as the many requests to deepen the discussion at the next training. Based on this experience, in the future it is possible to carry out blended community service activities by combining face-to-face and cyber-face methods, tailored to the availability of resources and objectives of activities. Training on financial technology can be proposed as material in the next period mentoring program.   Keywords: Financial Literacy, Online Training, Capacity Building, and Financial Life Skills  ABSTRAK Menyikapi kebijakan yang dikeluarkan pemerintah melalui Kementerian Pendidikan dan Kebudayaan tentang proses pembelajaran selama masa pandemi, perguruan tinggi menyesuaikan setiap bentuk kegiatan tridharma yang diselenggarakan, termasuk kegiatan pengabdian pada masyarakat. Salah satu kegiatan kerjasama antara Universitas Katolik Parahyangan dan Astra melalui program Kampung Berseri Astra dalam pelaksanaannya juga perlu disesuaikan. Salah satu bentuk kegiatan peningkatan kapasitas yang dilakukan tim pengabdi pada BUMDes Maju, Bumdes Jiwa Ilir dan BUMDes Bermuda di Kabupaten Indramayu adalah melalui penyelenggaraan pelatihan daring tentang literasi keuangan. Peserta terdiri dari pengelola BUMDES, UKM dan warga dari Desa Ujunggebang, Desa Ilir dan Desa Kedokanagung. Karena kegiatan dilaksanakan secara daring, sebagian peserta juga berasal dari mahasiswa dan UMKM di Jawa Barat.  Antusiasme para peserta tercermin keaktifan selama sesi pelatihan, banyaknya respon komentar dan pertanyaan yang disampaikan melalui chat box selama kegiatan berlangsung, serta banyaknya permintaan untuk memperdalam pembahasan pada pelatihan berikutnya. Berdasarkan pengalaman ini, maka di masa mendatang sangat dimungkinkan untuk dapat melaksanakan kegiatan pengabdian pada masyarakat dengan cara menggabungkan metode tatap muka dan tatap maya, disesuaikan dengan ketersediaan sumberdaya dan tujuan kegiatan. Pelatihan tentang financial technology dapat diusulkan sebagai materi pada program pendampingan periode selanjutnya.  Kata Kunci: Literasi Keuangan, Pelatihan Daring, Peningkatan Kapasitas, dan Financial Life          Skill